2023
DOI: 10.1371/journal.pone.0288680
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence and its associated factors among health care workers of a tertiary hospital in Kathmandu, Nepal

Anupama Bhusal,
Apekshya Adhikari,
Pranil Man Singh Pradhan

Abstract: Workplace violence (WPV) is a globally prevailing public health concerns among healthcare workers. Workplace violence includes occupational abuse (physical, sexual, verbal and psychological), threats or harm among health workers, and workplace harassment. It is important to identify the prevalence of workplace violence at the workplace. Therefore, this study aimed to assess workplace violence and its associated factors among healthcare workers at a tertiary hospital in Kathmandu, Nepal. A descriptive cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In this study, we found that nurses working in emergency departments had 4 times higher odds of experiencing workplace violence compared to those in outpatient departments. This finding is similar to that of a study conducted in Hawassa, Ethiopia (22), Eastern Ethiopia (11), Northwest Ethiopia (24), Rwanda (13), elsewhere in Iran (28), and in Kathmandu, Nepal (29). The possible reasons for the similarity could be due to the fact that emergency rooms are the more stressful and anxious areas for a client, the attendants, and the nurses, where unexpected events like deaths occurred and there was an absence of security.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we found that nurses working in emergency departments had 4 times higher odds of experiencing workplace violence compared to those in outpatient departments. This finding is similar to that of a study conducted in Hawassa, Ethiopia (22), Eastern Ethiopia (11), Northwest Ethiopia (24), Rwanda (13), elsewhere in Iran (28), and in Kathmandu, Nepal (29). The possible reasons for the similarity could be due to the fact that emergency rooms are the more stressful and anxious areas for a client, the attendants, and the nurses, where unexpected events like deaths occurred and there was an absence of security.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that the odds of workplace violence were 3 times higher among nurses working in inpatient departments compared to those who work in outpatient departments. This finding is supported by the results of studies conducted in Ethiopia (8,11,22,24,27) and a study done in Kathmandu, Nepal (29). This could be because of client pathologic conditions and waiting for a long time to get the service, which causes them to become irritated and dissatisfied and results in violence against nurses in the workplace.…”
Section: Discussionmentioning
confidence: 66%
“…This percentage aligns with previous studies conducted among healthcare professionals in Bangladesh, although it varies, with a lower prevalence of 43% reported by Shahjalal et al , 12 higher prevalence of 77.29% reported by Rony et al , 21 and compared with rates reported in studies conducted in Pakistan (53.4%), 22 India (63%) 23 and Nepal (45.5%). 24 …”
Section: Discussionmentioning
confidence: 99%
“…In future, HCWs should explain the rationale for triage and prioritization which can mitigate potential resentments and the workplace violence that often originates from poor communication and understanding of the medical procedures by patients and their caretakers [ 38 , 39 ]. Almost 50% of HCWs working in a tertiary care hospital in Nepal have experienced workplace violence, the perpetrators being the patients and their caretakers [ 40 ].…”
Section: Discussionmentioning
confidence: 99%